2016
DOI: 10.1080/07853890.2016.1193787
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime sleep duration and risk of nonalcoholic fatty liver disease: the Dongfeng-Tongji prospective study

Abstract: Long nighttime sleep duration was associated with a modestly increased risk of NAFLD in a middle-aged and elderly Chinese population. Key messages Long nighttime sleep duration was associated with a modestly increased risk of NAFLD in a middle-aged and elderly Chinese population. The effect of long nighttime sleep on the risk of incident NAFLD was attenuated greatly by body mass index (BMI) in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 52 publications
0
23
1
Order By: Relevance
“…Recently, the Dongfeng‐Tongji prospective study reported that long nightly sleep duration (8–9 and >9 h/day) is a significant risk factor for NAFLD, whereas no significant association was found between short nightly sleep duration (<7 h/day) and NAFLD, which is inconsistent with the findings of the present study. This discrepancy may be explained by the fact that the participants in the Dongfeng‐Tongji study were elderly retired employees (mean age 61.6 years); a different study population structure could generate dissimilar nightly sleep patterns, such as the sleep duration patterns shown in Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, the Dongfeng‐Tongji prospective study reported that long nightly sleep duration (8–9 and >9 h/day) is a significant risk factor for NAFLD, whereas no significant association was found between short nightly sleep duration (<7 h/day) and NAFLD, which is inconsistent with the findings of the present study. This discrepancy may be explained by the fact that the participants in the Dongfeng‐Tongji study were elderly retired employees (mean age 61.6 years); a different study population structure could generate dissimilar nightly sleep patterns, such as the sleep duration patterns shown in Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…Three studies showed short sleep duration to be associated with an increased risk of NAFLD, 18,35,36 whereas one Chinese prospective study showed long sleep duration (>8 hours) as a risk factor for NAFLD compared with 7-8 hours sleep duration in middle-aged and elderly people, although in men the association was attenuated after considering BMI. 20 In our study, short sleep duration was not associated with risk of liver cancer and the association between long sleep duration and liver cancer risk was attenuated slightly after obesity and diabetes were considered in the model. Approximately 2.5% of women reported having chronic liver diseases in our study population.…”
Section: Discussionmentioning
confidence: 42%
“…16 NAFLD has also been associated with short sleep duration and poor sleep quality, [17][18][19] as well as long sleep duration. 20 In a study conducted in Japan, the proportion of NAFLD was lowest in the group with a sleep duration of 6-7 hours and highest in the group with sleep durations of £6 and >8 hours in women. 21 The association between sleep duration and liver cancer has not been evaluated in an epidemiologic study.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, it is proposed that these metabolic alterations related to disrupted sleep patterns may be partially mediated by changes in gut microbiota [17,19]. Regarding the association of sleep duration and NAFLD, conflicting and often inconsistent results have been reported [15,20,21,22]. Thus, further investigation is needed to clarify this relationship.…”
Section: Introductionmentioning
confidence: 99%